Ascorbate-Deficient vtc2 Mutants in Arabidopsis Do Not Exhibit Decreased Growth - Lim, Benson; Smirnoff, Nicholas; Cobbett, Christopher S.; Golz, John F. (Frontiers in Plant Science, 2016)
In higher plants the L-galactose pathway represents the major route for ascorbate biosynthesis. The first committed step of this pathway is catalysed by the enzyme GDP-L-galactose phosphorylase and is encoded by two paralogs in Arabidopsis – VITAMIN C2 (VTC2) and VTC5. The first mutant of this enzyme, vtc2-1, isolated via an EMS mutagenesis screen, has approximately 20-30% of wildtype ascorbate levels and has been reported to have decreased growth under standard laboratory conditions. Here, we show that a T-DNA insertion into the VTC2 causes a similar reduction in ascorbate levels, but does not greatly affect plant growth. Subsequent segregation analysis revealed the growth defects of vtc2-1 mutants segregate independently of the vtc2-1 mutation. These observations suggest the presence of an independent cryptic mutation that affects growth in vtc2-1 mutants and that a 70-80% decrease in ascorbate is not sufficient to a dramatically alter plant growth as has been assumed in past studies.